Возможность применения немедленной имплантации с аугментацией кости и немедленной нагрузкой в реабилитации больных генерализованным пародонтитом - Гударьян, Александр Александрович; Ідашкіна, Наталья Георгієвна; Ширинкін, Сергій Володимирович; Чередник, Дмитро Олександрович (Actual Dentistry, 2019)
The current method of dental implantation for rehabilitation of patients with secondary adentia gaining popularity among doctors and patients. The purpose of the study: improving the efficiency of direct implantation with immediate loading in patients with generalized periodontitis of II–III degrees with direct bone regeneration. Materials and methods. The article presents the results of treatment of patients with generalized periodontitis of II III degrees by direct dental implantation with bone augmentation and immediate loading. Results. Revealed that the use of the method of direct implantation with direct bone augmentation and immediate loading in patients with generalized periodontitis has a high level of clinical success and has certain features. Conclusion. Revealed that this technique requires proper preoperative preparation (including local and general treatment), a differentiated approach in each case to the method of implantation and bone augmentation, as well as competent use and implementation of the protocol of immediate loading. Key words: generalized periodontitis, dental implantation, immediate loading, direct bone regeneration, bone augmentation.